2009
DOI: 10.1039/b912599j
|View full text |Cite
|
Sign up to set email alerts
|

Bond formations by intermolecular and intramolecular trappings of acylketenes and their applications in natural product synthesis

Abstract: The reactive intermediates known as acylketenes exhibit a rich chemistry and have been extensively utilized for many types of inter- and intramolecular bond-forming reactions within the field of organic synthesis. Characteristic reactions of acylketenes include cycloadditions, carbon–carbon bond-forming reactions, and nucleophilic capture with alcohols or amines to give β-keto acid derivatives. In particular, the intramolecular capture of acylketene intermediates with pendant nucleophiles represents a powerful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 57 publications
0
66
0
Order By: Relevance
“…61 When heated, a retro-hetero-Diels–Alder reaction could occur on the dioxenone moiety of 113 , and the resulting intermediate 114 would undergo a highly productive intramolecular ketene addition/Diels–Alder cascade to furnish an advanced hirsutellone scaffold ( 115 ) suitable for further modification. 62 …”
Section: Rapid Construction Of Hirsutellone Cores Featuring a Dioxmentioning
confidence: 99%
See 1 more Smart Citation
“…61 When heated, a retro-hetero-Diels–Alder reaction could occur on the dioxenone moiety of 113 , and the resulting intermediate 114 would undergo a highly productive intramolecular ketene addition/Diels–Alder cascade to furnish an advanced hirsutellone scaffold ( 115 ) suitable for further modification. 62 …”
Section: Rapid Construction Of Hirsutellone Cores Featuring a Dioxmentioning
confidence: 99%
“…The envisioned four-fragment strategy mentioned above proved amenable to the construction of a variety of advanced precursors, including 119 , 122 and 125, and each of these smoothly underwent the proposed dioxenone-opening/intramolecular Diels–Alder/intramolecular ketene-trapping sequence in respectable yields. 62,63 …”
Section: Rapid Construction Of Hirsutellone Cores Featuring a Dioxmentioning
confidence: 99%
“…[3d, 13,14] At the origin of this project, we were intrigued by the formation of isoxazolidinone 3a simply by mixing These bases displayed similar catalytic reactivity giving nearly 60% of conversion after 2 h (entries 2-4). Stronger bases such as DBU or triazabicyclo-…”
mentioning
confidence: 99%
“…Obviously, all these amines also possess a nucleophilic character, and it is conceivable that they react as such with Meldrums acid derivative 3a, through the formation of an acylketene species. [14,15] Nevertheless, when reactants 1a and 2a were subjected to sterically hindered and non-nucleophilic tetramethylpiperidine (TMP) a 41% of conversion was measured too (entry 7). Eventually, it was found that Hünigs base furnished the best result affording 64% isolated yield with 68% of conversion (entry 8).…”
mentioning
confidence: 99%
“…The Diels-Alder reaction, which has been reviewed extensively [44][45][46][47][48], provides a systematic way of introducing contiguous stereocenters with relative ease. One of the main advantages of the Diels-Alder cycloaddition is the overall understanding of its reactivity, selectivity, and methods for chiral induction.…”
Section: Cyclization Strategies To Hydrindane Coresmentioning
confidence: 99%